CHI '11 Extended Abstracts on Human Factors in Computing Systems 2011
DOI: 10.1145/1979742.1979646
|View full text |Cite
|
Sign up to set email alerts
|

The talking poles public art based in social design

Abstract: This case study provides insights for artists, designers, and technologists working with community-generated media in the domain of public art. The authors document their recent public artwork, the Talking Poles, and discuss the adaptation of Human Computer Interaction (HCI) design methods to the project. Community-generated public art has a direct relationship to the field of HCI through the technology that underlies both social computing and quotidian digital documentation. When acknowledging 'citizen action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…It was also celebrated for being a networked museum or repository for audio, written and visual recordings of current and past memories, narratives, works and ideas of local residents and others in the diaspora. While these benefits of community-generated digital art have been observed elsewhere (Moulder et al, 2011), the totem pole moved beyond its aesthetic and archival value to have a symbolic relevance to Wester Hailes as a community with historic problems of marginalisation. The general feeling among residents was that the totem pole served a symbolic function -that of community resilience and regeneration.…”
Section: Connecting Communities: Prospects and Risks For 'Big Society'mentioning
confidence: 94%
See 4 more Smart Citations
“…It was also celebrated for being a networked museum or repository for audio, written and visual recordings of current and past memories, narratives, works and ideas of local residents and others in the diaspora. While these benefits of community-generated digital art have been observed elsewhere (Moulder et al, 2011), the totem pole moved beyond its aesthetic and archival value to have a symbolic relevance to Wester Hailes as a community with historic problems of marginalisation. The general feeling among residents was that the totem pole served a symbolic function -that of community resilience and regeneration.…”
Section: Connecting Communities: Prospects and Risks For 'Big Society'mentioning
confidence: 94%
“…The community/human agency was also possible because the process of designing and producing the digital totem pole depended on the input of residents. As Moulder et al (2011: 2) observed during their 'Talking Poles' project, most public artwork that incorporate digital technology and produced by non-professional artists tended to exclude people from the final stages of the creative process. Our work, as with Moulder at al.…”
Section: Connecting Communities: Prospects and Risks For 'Big Society'mentioning
confidence: 99%
See 3 more Smart Citations